Analysis of the Influence of Compensation and Training on Employee Welfare with Organizational Culture as Moderation - Auliya, Fanny Rahma; Krismonia, Krismonia; Pebrianti, Winda (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This study aims to find out whether there is an effect of compensation and training on employee welfare with organizational culture as moderation in employees working in the Karawang area. The sampling method was used by distributing questionnaires to employees of manufacturing companies in the Karawang area with a sample of 112 respondents, then the data was analyzed using the Structural Equation Modeling (SEM-PLS) method. The results of this study state that compensation and training on employee welfare with organizational culture have a positive and significant effect. Meanwhile, compensation as a moderation for employee welfare and training as a moderation for employee welfare do not have a positive or significant influence on employee welfare on employees in the Karawang area.